The South Carolina Multigenerational Linked Birth Dataset: Developing Social Mobility Measures Across Generations to Understand Racial/Ethnic Disparities in Adverse Birth Outcomes in the US South. - Fleischer, Nancy L.; Abshire, Chelsea; Margerison, Claire E.; Nitcheva, Daniela; Smith, Michael G. (Maternal & Child Health Journal, 2019)
Objectives To describe the creation of a multigenerational linked dataset with social mobility measures for South Carolina (SC), as an example for states in the South and other areas of the country. Methods Using unique identifiers, we linked birth certificates along the maternal line using SC birth certificate data from 1989 to 2014, and compared the subset of records for which linking was possible with two comparison groups on sociodemographic and birth outcome measures. We created four multi-generational social mobility measures using maternal education, paternal education, presence of paternal information, and a summary score incorporating the prior three measures plus payment source for births after 2004. We compared social mobility measures by race/ethnicity. Results Of the 1,366,288 singleton birth certificates in SC from 1989 to 2014, we linked 103,194, resulting in 61,229 unique three-generation units. Mothers and fathers were younger and had lower education, and low birth weight was more common, in the multigenerational linked dataset than in the two comparison groups. Based on the social mobility summary score, only 6.3% of White families were always disadvantaged, compared to 30.4% of Black families and 13.2% of Hispanic families. Moreover, 32.8% of White families were upwardly mobile and 39.1% of Black families were upwardly mobile, but only 29.9% of Hispanic families were upwardly mobile. Conclusions for Practice When states are able to link individuals, birth certificate data may be an excellent source for examining population-level relationships between social mobility and adverse birth outcomes. Due to its location in the Deep South, the multigenerational SC dataset may be particularly useful for understanding racial/ethnic difference in social mobility and birth outcomes.